Neutrophil-to-Lymphocyte Ratio and Covid-19 Symptom-based Severity at Admission (Althea Medical Journal, 2021)
Background: Increased Neutrophil-to-Lymphocyte Ratio (NLR) is an independent risk factor for mortality in Covid-19 patients and is considered as an early warning sign of Covid-19 severity. This study aimed to observe the differences in NLR at admission between patients with mild, moderate, and severe symptoms of Covid-19 treated in a referral hospital in Banda Aceh, Indonesia.Methods:  A total of 114 patients with Covid-19 admitted to a referral hospital in Banda Aceh, Indonesia, during March–September 2020 were included in this study. Demographic information and baseline laboratory data, including the NLR, were collected. Descriptive and inferential statistics were used to analyze the data. Results: The median NLR at admission was higher among patients with moderate to severe symptoms than those with mild symptoms [6.54 (2.80–97.00, IQR 4.81–9.44) vs 2.27 (0.79–5.07, IQR 1.43-2.98), p
Keywords: Covid-19; neutrophil-to-lymphocyte ratio; symptoms severity